2020
DOI: 10.1021/acs.iecr.0c02773
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of CO2 on Metal-Based Cathode Electrocatalysts of Solid Oxide Electrolysis Cells

Abstract: Electrochemical reduction of CO2 using solid oxide electrolysis cells (SOECs) has emerged as an attractive approach for converting CO2 to high energy molecules, such as CO, a key precursor for the synthesis of fuels and chemicals using the commercially established Fischer–Tropsch process. The in situ generation of syngas (CO and H2) has also been demonstrated in SOECs through the coelectrolysis of CO2 and H2O. However, conventional Ni-based SOEC cathodes exhibit high overpotential losses associated with CO2 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…Obviously, the current density sharply drops from 900 to 681 mA cm –2 in the first 1.5 h, and then, a slight degradation of current density was observed during the test. The fast degradation at beginning is likely associated with the strong oxygen binding of metallic Fe . In addition, the slight decrease might be owing to partial oxidation of Fe nanoparticles and destruction of the cathode microstructure at elevated temperature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Obviously, the current density sharply drops from 900 to 681 mA cm –2 in the first 1.5 h, and then, a slight degradation of current density was observed during the test. The fast degradation at beginning is likely associated with the strong oxygen binding of metallic Fe . In addition, the slight decrease might be owing to partial oxidation of Fe nanoparticles and destruction of the cathode microstructure at elevated temperature.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that Fe has a strong oxophilicity, which is related to the strength of metal-oxygen bonding. The metallic Fe is, therefore, often present in the form of alloy in the nanoparticles . For instance, the enhanced stability of Ni particles and decreased diffusion resistance were achieved after addition of Fe in the metallic Ni, resulting in a high electrolysis current density of −1840 mA cm –2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fresh water mixed with recycled condensate is pressurized by a pump and fed into the cathode heat exchanger (heater model). Part of the product gas of the cathode is recycled and mixed with inlet gas to maintain the hydrogen content of the inlet gas at ∼10% to prevent nickel from being oxidized at the cathode . The mixture of steam and hydrogen is heated in cathode heat exchange to meet the operating temperature of the SOEC.…”
Section: System Description and Modelingmentioning
confidence: 99%
“…Part of the product gas of the cathode is recycled and mixed with inlet gas to maintain the hydrogen content of the inlet gas at ∼10% to prevent nickel from being oxidized at the cathode. 33 The mixture of steam and hydrogen is heated in cathode heat exchange to meet the operating temperature of the SOEC. The rest of the product gas of the cathode is used as the hydrogen source of the EGS unit, which is mainly modeled by the RPlug and five RadFrac models.…”
Section: Ohmic Overpotential (η Ohm )mentioning
confidence: 99%